A multi-agent architecture for intelligent data analysis - Queiroz, Jonas F.P. [UNESP]; Guilherme, Ivan Rizzo [UNESP]; Batista, Caio Cesar [UNESP] (My University, 2011)
The present study introduces a multi-agent architecture designed for doing automation process of data integration and intelligent data analysis. Different from other approaches the multi-agent architecture was designed using a multi-agent based methodology. Tropos, an agent based methodology was used for design. Based on the proposed architecture, we describe a Web based application where the agents are responsible to analyse petroleum well drilling data to identify possible abnormalities occurrence. The intelligent data analysis methods used was the Neural Network.
Keywords: Intelligent data analysis; Multi-agent architecture; Web based application; Agent-based methodologies; Automation process; Data integration; Multi-Agent; Multiagent architecture; Proposed architectures; Web-based applications; Automation; Data reduction; Information science; Neural networks; Oil wells; Robotics; User interfaces; Well drilling; Network architecture